Correlation of Visual Acuity To Average Report Card Scores with High Index Scale Assessment of Grade 2 Students of Muhammadiyah 01 Medan Senior High School - Muhammad Fathan Arsya; Zaldi Z (International Journal of Health and Pharmaceutical (IJHP), 2026)
Introduction: The eyes are important human senses for carrying out daily activities. Vision impairment is common and can be at risk of causing blindness. Globally, about 2.2 billion people have vision impairments, and more than 1 billion of them are preventable. Children aged 5-15 years are also affected, with 19 million of them experiencing visual impairments. Impaired visual acuity in children can affect their academic performance, as poor vision interferes with learning ability. The sharp decline in vision during the COVID-19 pandemic was exacerbated by excessive use of gadgets, leading to worsening visual impairment. If not treated appropriately, this disorder can hinder a child's development. Vision examination is essential to detect this problem early, and examination with the Snellen Chart is one of the effective methods in detecting such abnormalities. Objective: This study aims to see the relationship between the level of visual acuity and the average score of report cards in grade 2 students of SMA Muhammadiyah 01 Medan. Methods: The study used an analytical descriptive design with a cross-sectional approach. The research sample consisted of 71 2nd grade students of Muhammadiyyah Private High School 01 for the 2024/2025 school year. The sharpness of the vision was checked using the Snellen Chart, while the average score of the report card was taken from the student's academic data. Data analysis was carried out using the Chi-square test. Results: The majority of the research subjects based on the classification of the average score of the report card for normal vision were very good with the number of 17 samples (65.38%) and for the abnormal vision was good with the number of 15 samples (60%). The results of the Chi-square test obtained a p value of 0.042. Conclusion: There is a significant relationship between the level of visual acuity and the average score of the report card of students of SMA Muhammadiyah 01 Medan.